Planeación financiera a la empresa “Importadora Ortega Cía. Ltda.” de la ciudad de Loja, periodo 2023-2027 - Sánchez Romero, Anibal Javier (2023)
The present Curricular Integration Work "Financial Planning for Importadora Ortega Cía. Ltda., a company located in the city of Loja, during the period 2023- 2027," was developed with the purpose of implementing the use of a financial tool such as Financial Planning, according to the economic activities naturally carried out by the company, which allows providing a significant contribution to the administrative staff of the company. To fulfill the specific objectives, it began with the collection of information and financial statements of the company for the years 2020 and 2021, which provide insight into the economic and financial situation. A forecast of purchases and sales was developed in order to determine the projected economic results, which allows maximizing opportunities, minimizing risks, and using historical sales and purchases data from 2020 and 2021 as the base information. These data were used to project from 2023 to 2027, taking into account that 2022 could not be projected since this work was conducted in mid-2022. By applying the incremental percentage method, the monthly increase was determined, which allowed identifying that the months in which the company sells the most are March, May, August, and December. Next, a cash budget was prepared to forecast future cash inflows and outflows for the company and to anticipate any future situations that may arise. This was done by considering the cash inflow and outflow programs, applying the percentage of income and expense increments, and taking into account the projected sales and purchases for the study years. Cash outflows also considered, in addition to the aforementioned factors, salaries and wages from 2020 and 2021 to calculate salary increase percentages and other social benefits. Subsequently, the Proforma Income Statement and Financial Position were prepared to determine the expected revenues, costs, and expenses for the subsequent years, increasing each year according to the volume of projected sales. Finally, the Break- Even Point for the projected years was determined, allowing for the assessment of the company's profitability for future years. Finally, conclusions and recommendations are described based on the obtained results. It is concluded that Importadora Ortega Cía. Ltda. does not have long-term 5 financial planning, a cash budget, sales forecasts, as well as sales and collection policies, which hinders the ability to assess the future financial situation for decision- making purposes, including prevention and increasing economic and financial profitability.